Flotation separation of quartz from apatite and surface forces in bubble–particle interactions: Role of pH and cationic amine collector contents - Han, Yosep; Han, Seongsoo; Kim, Byeongwoo; Yang, Jiwon; Choi, Junhyun; Kim, Kwanho; You, Kwang-Suk; Kim, Hyunjung (Journal of industrial and engineering chemistry (Seoul, Korea), 2019)
[Display omitted] •Selective separation of quartz from apatite can be obtained using the collector at pH 3.•Adsorption of the collector on the mineral surface occures by electrostatic attraction.•Higher selective separation obtained due to higher adsorption of collector on quartz surface.•Hydrophobic interaction energy improved due to the collector adsorbed on the quartz surface.•Quartz particle can be reversely floated efficiently by high hydrophobicity interaction. Dodecylamine hydrochloride (DAHC) surfactant was used as a collector for effective apatite recovery through flotation separation in siliceous phosphate ore, wherein quartz is the main gangue mineral. The roles of pH and collector concentration were investigated, and the adsorption of the collector on the minerals and related properties were systematically studied by measuring zeta potential, contact angle, surface tension, and adsorption density. When the collector concentration was 5×10−5M, 23.7% P2O5 grade was achieved for a conditioning time of 10min. However, the separation performance of the flotation was lower at pH 7 regardless of the collector concentration. Thus, more collector molecules are adsorbed on the quartz surface than the apatite surface at pH 3 and 5×10−5M of collector, resulting in separation of quartz and apatite. The extended Derjaguin–Landau–Verwey–Overbeek (DLVO) theory, which considers the hydrophobic interaction energy, revealed that the improved flotation performance is attributed to a hydrophobic attractive force that is a consequence of the collector adsorption. Therefore, the results of flotation of artificially mixed minerals further revealed that optimization of the amine collector concentration and pH value can selectively separate quartz from apatite.